FSKM online examination management system (FOEMS) / Ahmad Saifullah Ahmad Tarmize - Ahmad Tarmize, Ahmad Saifullah (2011)
Examination is compulsory usually for every subject that was offered in the university and it is a job of the university or faculty to manage the examination papers to ensure that the examination papers are appropriate for the student to test their skills and suitable for the lecturers to grade the student according to their knowledge. The aim of this project is to develop and implement web application system FSKM Online Examination Management System (FOEMS) to process examination paper making in FSKM, stepping stone in enhancing the Examination Paper Bank Management System (EPBMS) with new functionality and features. This project will focus on examination paper department in FSKM which the system will manage the process of making examination papers in FSKM only. In essence, analysis and study to research about the problem for the FOEMS system is done by analyzing the current manual system and EPBMS to come out with a new requirement to add functionality and features to the FOEMS such as the functionality to send notification to the Vetors to check the examination papers. Therefore, this project is proposed to overcome the current problem and ensure the capability of the system to satisfy user’s requirement and business flow. This project is following the System Development Life Cycle (SDLC) framework or also known as Waterfall Model. As a result of this project, head of department can assign lecturers to make the examination papers and vetors can check for the examination papers that have been submitted to the examination department because the system will automatically send notification to them. It is hope that this system will helps the examination department to manage the process efficiently.